A Student Self-Presentation: A Dramaturgical Study of Student Regarding the Prohibition of Seclusion - Saputri, Rimadini; Subaidi (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2026)
Islamic boarding schools (pesantren) are educational institutions that primarily focus on moral guidance and Islamic religious knowledge. One of the rules is the prohibition of silence or dating for students within the pesantren environment. This study was conducted to determine the forms of dramaturgy carried out by students to circumvent these rules. This type of research is qualitative research with data collection methods through interview techniques. The theory used to analyze the interview results is the dramaturgy theory proposed by Erving Goffman. The results of this study are divided into two types of informants: students who do not have access to outside the pesantren and technology and students who have access to both. This study shows that the behavior of students who comply with the rules in the foreground is to avoid unnecessary interactions with students of the opposite sex. The behavior in the background shown by students who do not have access to outside the pesantren and technology is to make secret contact with students of the opposite sex. Students who have access to outside the pesantren and technology meet outside the pesantren environment, while within the pesantren they still maintain contact with their partners through instant messaging applications.